Oxygen gradient ektacytometry does not predict pain in children with sickle cell anaemia. (3rd December 2021) - Nardo‐Marino, Amina; Petersen, Jesper; Brewin, John N.; Birgens, Henrik; Williams, Thomas N.; Kurtzhals, Jørgen A. L.; Rees, David C.; Glenthøj, Andreas
Summary: The loss of red blood cell (RBC) deformability in sickle cell anaemia (SCA) is considered the primary factor responsible for episodes of acute pain and downstream progressive organ dysfunction. Oxygen gradient ektacytometry (Oxygenscan) is a recently commercialised functional assay that aims to describe the deformability of RBCs in SCA at differing oxygen tensions. So far, the Oxygenscan has been evaluated only by a small number of research groups and the validity and clinical value of Oxygenscan‐derived biomarkers have not yet been fully established. In this study we examined RBC deformability measured with the Oxygenscan in 91 children with SCA at King's College Hospital in London. We found a significant correlation between Oxygenscan‐derived biomarkers and well‐recognised modifiers of disease severity in SCA: haemoglobin F and co‐inherited α‐thalassaemia. We failed, however, to find any independent predictive value of the Oxygenscan in the clinical outcome measure of pain, as well as other important parameters such as hydroxycarbamide treatment. Although the Oxygenscan remains an intriguing tool for basic research, our results question whether it provides any additional information in predicting the clinical course in children with SCA, beyond measuring known markers of disease severity.